Criminal Law Policies in an Effort to Tackle Criminal Acts of Terrorism Financing - M. Arief Amrullah (Faculty of Law, University of Merdeka Malang, 2023)
The issues that will be discussed in this research include what are. This research was initiated by the development of terrorist groups that request donations from individuals or groups or foundations, or corporations. Likewise, this writing aims to prevent the collection of funds to finance terrorist activities using corporations. Identifying Beneficial Owners of Corporations is very important in preventing criminal acts of terrorism financing. This article uses normative legal research methods. The sources of legal materials used are primary legal materials and secondary legal materials. The procedure for collecting legal materials in this article is to study library materials. Analysis of legal material sources was carried out descriptively. Empowering in its concretization, legal products related to terrorism funding need to be harmonized and renewed. Because of this, the existing law should be updated to suit developments and the modus operandi of terrorist organizations in raising funds so that the abuse of corporations as a vehicle for committing criminal acts of terrorism funding can be prevented and eradicated.How to cite item: Amrullah, M. Arief, â€œLegal Problems Related to Mineral and Coal Mining Permits.â€ Jurnal Cakrawala Hukum 14 no. 1 (2023): 86-95. DOI: 10.26905/idjch.v14i1.9881.